What determines fiscal policy?: evidence from German states - Helge Berger; Anika Holler (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper explores the factors behind the time path of real spending and revenue in the West German states from 1975 to 2004. The empirical approach stresses robustness and takes into account a large set of economic and political variables. Our results suggest that common economic factors and, to a smaller degree, state-specific economic developments are important determinants of state fiscal performance. In comparison, the influence of political factors is limited both in statistical and quantitative terms. Finally, there is evidence that addressing governance problems and ensuring flexibility in terms of fiscal strategy are important ingredients for any policy aimed at improving fiscal outcomes at the state level.
Keywords: D72; E62; H62; H63; 330; Finanzpolitik; Länderhaushalt; Wirtschaftswachstum; Public Choice; Governance-Ansatz; Schätzung; Deutschland